The Effect of Price and Promotion on Customer Satisfaction With Service Quality as a Mediating Variable at Leslie Rent Car in Medan - Daniel Leslie; Jarungjung Hutagaol (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study examines the effect of price and promotion on customer satisfaction with service quality as a mediating variable at Leslie Rent Car in Medan. The research was designed to identify the main factors that shape customer satisfaction in the car rental service sector and to test whether service quality acts as an important mechanism linking marketing variables to customer satisfaction. A quantitative approach was employed using survey data collected from 382 active customers of Leslie Rent Car in Medan. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS), including measurement model evaluation, structural model testing, and hypothesis testing. The results show that all indicators met the requirements of convergent validity, discriminant validity, and reliability, indicating that the measurement model was acceptable. In the structural model, customer satisfaction was explained by price, promotion, and service quality with an R-square value of 0.510, while service quality was explained by price and promotion with an R-square value of 0.035. Hypothesis testing revealed that price had a positive and significant effect on service quality and customer satisfaction. Service quality also had a positive and significant effect on customer satisfaction and was found to be the strongest predictor in the model. In addition, service quality significantly mediated the relationship between price and customer satisfaction. However, promotion did not have a significant effect on service quality or customer satisfaction, and service quality did not mediate the effect of promotion on customer satisfaction. The study concludes that customer satisfaction at Leslie Rent Car is primarily influenced by fair and appropriate pricing as well as the actual quality of service experienced by customers. Service quality plays a central role in transforming price perceptions into customer satisfaction, while promotion alone is not sufficient to improve either service quality or satisfaction. These findings suggest that improving vehicle condition, punctuality, staff friendliness, driver competence, and special attention should become the company’s primary strategic focus.